Bottled vs. Canned Beer: Do They Really Taste Different? - Andrew Barnett; Carlos Velasco; Charles Spence (Beverages, 2016)
People often say that beer tastes better from a bottle than from a can. However, one can ask how reliable this perceived difference is across consumers. And, if reliable, one can further ask whether it is a purely psychological phenomenon (associated with the influence of packaging on taste perception), or whether instead it reflects some more mundane physico-chemical interaction between the packaging material (or packing procedure/process) and the contents. Two experiments were conducted in order to address these questions. In the main experiment, 151 participants at the 2016 Edinburgh Science Festival were served a special ‘craft beer’ in a plastic cup. The beer was either poured from a bottle or can (a between-participants experimental design was used). The participants were encouraged to pick up the packaging in order to inspect the label before tasting the beer. The participants rated the perceived taste, quality, and freshness of the beer, as well as their likelihood of purchase, and estimated the price. All of the beer came from the same batch (specifically a Session IPA from Barney’s Brewery in Edinburgh). None of the participants were familiar with this particular craft brew. Nevertheless, those who evaluated the beer from the bottle rated it as tasting better than those who rated the beer served from the can. Having demonstrated such a perceptual difference (in terms of taste), we then went on to investigate whether people would prefer one packaging format over the other when the beer from bottle and can was served blind to a new group of participants (i.e., when the participants did not know the packaging material). The participants in this control study (n = 29) were asked which beer they preferred. Alternatively, they could state that the two samples tasted the same. No sign of a consistent preference was obtained under such blind tasting conditions. Explanations for the psychological impact of the packaging format, in terms of differences in packaging weight (between tin and glass), and/or prior associations of quality with specific packaging materials/formats (what some have chosen to call ‘image molds’), are discussed.